1997
DOI: 10.1002/(sici)1098-2345(1997)42:4<253::aid-ajp1>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Social and reproductive conditions modulate urinary cortisol excretion in black tufted-ear marmosets (Callithrix kuhli)

Abstract: The links between psychosocial stress, social status, reproductive function, and urinary cortisol were assessed in social groups of black tuftedear marmosets (Callithrix kuhli). Urinary cortisol excretion was monitored in cases of intrafamily conflict ("sibling fights") and in daughters in four distinct social contexts: in the family group, while housed singly or in same-sex pairs, and while paired with a male pairmate. Cortisol excretion was elevated in participants in intra-family conflict on the day of and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 55 publications
4
32
0
Order By: Relevance
“…In this sense, Smith and French (1997) evaluating the behavioral pattern of heterosexual pairmates in C. kuhli to social deprivation found that the presence of partners reduced the behavioral response of exposure to novelty (new cage). On the other hand, individuals housed alone in the new cage spent more time in close proximity to their pairmates when returned to their home cage.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this sense, Smith and French (1997) evaluating the behavioral pattern of heterosexual pairmates in C. kuhli to social deprivation found that the presence of partners reduced the behavioral response of exposure to novelty (new cage). On the other hand, individuals housed alone in the new cage spent more time in close proximity to their pairmates when returned to their home cage.…”
Section: Discussionmentioning
confidence: 89%
“…The main glucocorticoid found in primates is cortisol, which is released during behavioral stress (Sapolsky 1993). Cortisol assays have been widely used to determine the effects of both acute (Smith and French 1997) and chronic stress on captive primates, including alterations in captive conditions (Johnson et al 1991;Crockett et al 2000;Cross et al 2004) and maternal separation or peer group formation (Terao et al 1995). Moreover, studies with non-human primates showed a relationship between elevated cortisol and social deprivation (Callicebos moloch: Mendoza and Mason 1989), reduction of physical space (Macaca mulatta: Hassler et al 1989) and exposure to novel environments (Saimiri sciureus: Mendonza 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Lerchl et al, 1991;Muller and Lipson, 2003;Smith and French, 1997). Therefore, time of urine collection is a variable that needs to be controlled for.…”
Section: Diurnal Variation and Urine Collectionmentioning
confidence: 99%
“…Concerning urinary measurements, quantification of urinary cortisol has been shown to provide a reliable method for monitoring stress hormone output in a variety of primate species (Crockett et al, 1993;Robbins and Czekala, 1997;Smith and French, 1997;Whitten et al, 1998b). Since native cortisol is, however, quantitatively of little importance, measurement of the more abundant 5β-reduced cortisol metabolites might at least in some species be more suitable (Bahr et al, 2000;Klinkova et al, 2008).…”
Section: Examples Of Applicationmentioning
confidence: 99%
“…Blunted HPA axis responses to a novel environment have also been reported in socially bonded female guinea pigs [53]. Furthermore, female black tufted-ear marmosets (Callithrix kuhli) that are removed from the natal family group and housed alone in a novel environment exhibit a significant increase in cortisol concentration unless housed with a familiar sibling upon separation from the rest of the family [54]. Socially isolated female squirrel monkeys (Saimiri sciureus) also have higher basal and stress-induced circulating cortisol concentrations than pair-housed monkeys [55].…”
Section: Effects Of Prosocial Behavior On the Hpa Axismentioning
confidence: 99%